Inside Front Cover: Extracellular vesicle‐coated nanoparticles (View 2/2021). Issue 2 (8th April 2021) - Fathi, Parinaz; Rao, Lang; Chen, Xiaoyuan
Abstract : In article number 20200187, Parinaz Fathi, Xiaoyuan Chen and their co‐workers have displayed a "Giftwrapping Nanoparticles" scene where coating nanoparticles with extracellular vesicles enables their targeted uptake.